Influence of Coconut Husk Biochar and Inter-Electrode Distance on the No-Load Voltage of the Cymbopogan citratus Microbial Plant Fuel Cell in a Pot - Epiphane Zingbe; Damgou Mani Kongnine; Bienvenu M. Agbomahena; Pali Kpelou; Essowè Mouzou (Electrochem)
In a plant microbial fuel cell (P-MFC), the plant provides the fuel in the form of exudates secreted by the roots, which are oxidised by electroactive bacteria. The immature plant is hampered by low energy yields. Several factors may explain this situation, including the low open-circuit voltage of the plant cell. This is a function of the development of the biofilm formed by the electroactive bacteria on the surface of the anode, in relation to the availability of the exudates produced by the roots. In order to exploit the fertilising role of biochars, a plant cell was developed from C. citratus and grown in a medium to which 5% by mass of coconut shell biochar had been added. Its effect was studied as well as the distance between the electrodes. The potential of Cymbopogon citratus was also evaluated. Three samples without biochar, with inter-electrode distances of 2, 5 and 7 cm, respectively, identified as SCS2, SCS5 and SCS7, and three with the addition of 5 % biochar, with the same inter-electrode distance values, identified as S2, S5 and S7, were prepared. Open-circuit voltage (OCV) measurements were taken at 6 a.m., 1 p.m. and 8 p.m. The results showed that all the samples had high open-circuit voltage values at 1 p.m. Samples containing 5% biochar had open-circuit voltages increased by 16 %, 8.94% and 5.78%, respectively, for inter-electrode distances of 2, 5 and 7 cm compared with those containing no biochar. Furthermore, the highest open-circuit voltage values were obtained for all samples with C. citratus at an inter-electrode distance of 5 cm. The maximum power output of the PMFC with C. citratus in this study was 75.8 mW/m2, which is much higher than the power output of PMFCs in recent studies.